First Information Report (FIR) as a Distinct Genre of Legalese: A Corpus-based Forensic Analysis - Shaheen-ul-Zaman; Aziz Ullah Khan; Ayyaz Mahmood (University of Chitral Journal of Linguistics and Literature, 2024)
Forensic linguistics deals with the use of linguistic knowledge to help solve crimes. It is an interface between language, crime, and the law. A First Information Report (FIR) is the first step in the criminal justice system to decide crimes. The language used in an FIR has wide implications in the process of administration of justice. This study was conducted to investigate how the language of FIRs is distinctive as compared to ordinary discourse, thereby constituting a genre. It further explored the characteristic linguistic features of FIRs. The data consisted of 126 FIRs (in English) registered in different police stations of Islamabad Capital Territory (ICT) during the year 2013. A small corpus of FIRs was then developed for the analysis of the language of FIRs. The methodology for the study was developed by synthesizing Genre Theory, Corpus-based strategies in linguistics research, and Forensic Linguistics. Data was analyzed at the macro level to determine the structure of FIRs. It was found that the main part of the FIR comprised the narrative in which complainants told their stories to the police officers. Linguistic features of FIRs at a micro level were analyzed with the help of methods devised in the light of previous research in discourse analysis. Distinctive linguistic features of FIRs were noted with the help of the electronic software AntConc. Findings of the analysis of the structure and the language of the FIRs point to the fact that FIRs are a separate genre in legal discourse, with distinct textual and textural features and moves. This study may be helpful to the law majors, the new entrants in the police department, and the teachers teaching English for occupational purposes.